Analisis Potensi Pajak Daerah Sebagai Sumber Pendapatan Asli Daerah di Kabupaten Tanjung Jabung Barat - Pantun Bukit; Hana Tamara Putri (Universitas Batanghari Jambi, 2018)
Tax areas as one of the components of the Original Local Revenue (PAD) which is given by the local Government to residents who stay in their jurisdiction without obtaining the consideration from the local governments that collect taxes area. Tanjung Jabung Barat District is one of the strategic areas and it has a potential of natural resources which is relatively large. The strategies and policies of financial development in Tanjung Jabung Barat is directed at the improvement of the effectiveness as well as the effectiveness of regional finance. One of the strategies is through the optimization of local tax receipts as a source of Original Local Revenue (PAD). This research aimed at investigating the magnitude of the potential and the local tax capacity in Tanjung Jabung Barat District of 2018. This research also intended to know the implementation of tax effort which has been attempted in Tanjung Jabung Barat District. Last, this research aimed at knowing the extent to which the original revenue dependency area toward the acceptance of tax areas in Tanjung Jabung Barat District.The data were collected through survey and direct observation to the research subject through the coordination with related agencies. In data analysis method, Diagrams Cartesius, Regression approach to Tax Business, Estimation and Elasticity Tax Formulas, analysis of Overlay and analysis of Potential local tax were used. The results of this research are expected to give input to the Government of Tanjung Jabung Barat in arranging the strategies and policies in optimizing the Local Tax Revenue.